Association between contextual factors and vaccine coverage against human papilomavirus in adolescents in the state of Minas Gerais, Brazil: global spatial regressions - Bianca Maria Oliveira Luvisaro; Thales Philipe Rodrigues da Silva; Josianne Dias Gusmão; Marcela Lencine Ferraz; Luciana Maiara Diogo Nascimento; Larissa Pereira Gomes; Fernanda Penido Matozinhos (BMC Infectious Diseases)
Abstract This study aimed to identify the associations between socioeconomic factors, the social environment, and human papillomavirus (HPV) vaccine coverage among adolescents in the state of Minas Gerais (MG), Brazil. This ecological study utilized secondary data from 853 municipalities in MG, covering female adolescents from 2014 to 2022 and male adolescents from 2017 to 2022, as provided by the information system of the National Immunization Program. Spatial statistical analysis was conducted to assess spatial dependence and identify spatial clusters of municipalities with high and low HPV vaccine coverage. The first and second dose coverage among male adolescents in most municipalities in MG was classified as very low (< 50%) or low (≥ 50% to < 80%). Among female adolescents, the majority of coverage rates were adequate (≥ 80%) or low (≥ 50% to < 80%). Socioeconomic factors, area-specific factors, and their interactions may influence HPV vaccination rates. The disparities in vaccination coverage rates observed across the state highlight the need for targeted interventions to increase coverage and reduce health issues, such as cervical cancer.